Prognostic factors in systemic sclerosis - Górecka, Aleksandra; Szymańska, Elżbieta; Walecka, Irena (Dermatology Review/Przegląd Dermatologiczny, 2023)
Systemic sclerosis is a chronic disease involving the connective tissue of the skin and internal organs. It is characterised by disorders of peripheral microcirculation, immune dysregulation, and deposition of collagen fibres and other substances in connective tissue. The most common organ complications in systemic sclerosis include interstitial lung disease, pulmonary arterial hypertension, renal tubular hypertrophy, and arthritis. Imaging findings often precede clinical symptoms, so all patients should be screened as soon as possible, preferably in the asymptomatic phase of the disease. Treatment options for systemic sclerosis include immunomodulatory therapies as well as therapeutic modalities targeting vascular mechanics and connective tissue fibrosis. Efforts are underway to discover new, more sensitive and specific prognostic factors that would help to personalize therapies and thus improve the final treatment outcomes. Identified biomarkers would accelerate the implementation of appropriate treatments, delaying the progression of irreversible complications and decreasing mortality rates in patients.